2021
DOI: 10.1200/go.21.00228
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Clinical Outcomes of Brazilian Patients With Stage III or IV Non–Small-Cell Lung Cancer: Real-World Evidence Study on the Basis of Deterministic Linkage Approach

Abstract: PURPOSE Non–small-cell lung cancer (NSCLC) is the most common type of lung cancer and accounts for 80%-90% of the cases. In Brazil, between 2018 and 2019, lung cancer was ranked as the second most frequent cancer among men and the fourth among women. The primary objectives were to describe the journey and survival rates of patients with advanced NSCLC treated in the Brazilian private health care system (HCS). MATERIALS AND METHODS A retrospective cohort study was based on the search in administrative databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…For example, in a 2005 survey, the number of CT scanners per 1 000 000 population was 4.9 and 30.8 in public and private cancer hospitals in Brazil in 2005, respectively, showing the difficulties in accessing an adequate diagnostic evaluation in public cancer hospitals. However, the number of CT scanners was quite comparable to those in the best‐developed countries, such as the United States and Japan (31.5 and 32.2, respectively) 36–38 …”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…For example, in a 2005 survey, the number of CT scanners per 1 000 000 population was 4.9 and 30.8 in public and private cancer hospitals in Brazil in 2005, respectively, showing the difficulties in accessing an adequate diagnostic evaluation in public cancer hospitals. However, the number of CT scanners was quite comparable to those in the best‐developed countries, such as the United States and Japan (31.5 and 32.2, respectively) 36–38 …”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, we believe that over the years, the disparity in access to health care, which is a real problem in our region, has decreased. At the same time, multi- [36][37][38] Another example was that in Brazil, PET was approved for lung cancer staging in 2010 and was promptly incorporated in private cancer hospitals; however, in public cancer hospitals, the same technology was incorporated only in 2014. 37,38 According to recent statistics, 71.1% of the Brazilian population depends on the public healthcare system to have access to cancer treatment, whereas 28.4% of people have access to private cancer hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike other studies that included patients enrolled in RCTs, our study included real-world patients who were treated according to drugs approved by the Brazilian regulatory agency and available to the population at the time of the study. Thus, the lower proportion of patients treated in the first line with ICI may point to barriers in the access to immunotherapy and this issue is discussed in the literature (24). Finally, the fact that most of our patients had primary lung cancer may have influenced our analysis, whereas most studies have shown positive results in cohorts of patients with melanoma, renal cell carcinoma, and lung cancer (8, 9, 12, 14-16).…”
Section: Discussionmentioning
confidence: 98%